Development of coconut fiber reinforced cement composites with the addition of fly ash - Nur Izzati Muhammad Nadzri (School of Materials Engineering, Universiti Malaysia Perlis, 2012)
The main purpose is to develop coconut fiber reinforced cement composites with the addition of fly ash aims are: i-To develop lightweight and high strength of coconut fiber reinforced cement composites with the addition of fly ash for application in contruction. ii- To study the effect of coconut fiber as the reinforcement and fly ash as sand replacement material in the cement composites on mechanical and physical properties. iii- To investigate the crack profile and fracture behavior of the cement composites.